Circular Subwavelength Photodetectors for 3D Space Exploration. Issue 6 (13th January 2022) - Pan, Qi; Sun, Yali; Su, Meng; Chen, Sisi; Cai, Zheren; Zhang, Zeying; Zou, Miaomiao; Chen, Bingda; Mikhailova, Julia V.; Zuev, Dmitry; Song, Yanlin
Abstract: Detectors with the ability of 3D space exploration greatly promote sensing performance for artificial intelligence, automatic drive, etc. Current photodetectors for spatial angle detection are usually composed of planar stacked light‐sensing elements on the bulky 3D configuration. To meet the miniaturization and integration of intelligent systems, it is critical to break the obstacle between chip‐level architecture and spatial recognition function. Here, a chip‐level circular facade photodetector for 3D space exploration is demonstrated. The template used in the miniature solid‐shaping strategy guides the photosensitive materials patterning into 3D circular configuration, which divides the space into equal subdivisions. The multi‐directional light‐coupling interaction from the circular structure and the wider light–matter resonance from the self‐standing facade endow the 3D photodetectors with the capability of wide detection range (horizontal: 360°; vertical: 60°) and high detection accuracy (99.6%). Furthermore, this work provides a novel approach for 3D optoelectronics in intelligent systems. Abstract : A 3D subwavelength circular photodetector is demonstrated via the miniature solid‐shaping strategy, which achieves wide detection space angle and precise spatial recognition. The circular photodetector provides a novel model for multi‐angle detection in the applications of automatic drive, robot vision, and augmented reality.